COMPARISON OF HONEY EFFECTIVNESS WITH SILVER SULFADIAZINE 1% ON THE FORMATION OF EPITHELIAL POST DEEP DERMAL BURNS INJURY AT RATS - Chandra Boby Hadinata; Abda Arif; Irfannudin Irfannudin (Fakultas Kedokteran Universitas Sriwijaya, 2020)
This study is an experimental animal study that assesses the difference in effectiveness of healing deep dermal burns using 1% honey and silver sulfadiazine. The subjects of this study were rats that had deep dermal burns on their backs which were then treated with 1% honey and silver sulfadiazine. Then the epithelialization thickness was measured using a microscope. In this study, the results showed that in the honey administration group epithelium occurred with an average of 1.111±0.298 or 49.42%, whereas in the silver sulfadiazine 1% cream group epithelium had occurred with an average of 1,100 ±0.336 or 50.57%. There was no statistically significant difference between honey epithelium with silver sulfadiazine cream 1% on the 4th day with a value of ? = 0.921. In the Honey giving group epithelium occurred with a mean of 1.496±0.225, meaning that the epithelium increased by 20.92 ± 5.57%. In the group giving 1% silver sulfadiazine cream epithelium occurred on the 7th day with a mean of 1.362±0.166, meaning that the epithelial increase was 16.12 ± 10.42%. There were no statistically significant differences on the 7th day epithelium with a value of p = 0.171. Comparison of 10th day Epithelial Thickness between Honey Giving Group and SSD cream 1%, In the Honey group, epithelium occurred with an average of 1.746 ± 0.314, meaning that the epithelium increased by 12.12 ± 2.02%, whereas in the silver sulfadiazine 1% group, epithelium occurred with an average of 1.758 ± 0.244, meaning that the epithelium increased by 12.12 25 ± 0.89%. There was no statistically significant difference in epithelium on the 10th day with a value of p = 0.926. Honey and Silver 1% sulfadiazine cream have the same effectiveness against epithelial formation in deep dermal burns. Giving honey can be recommended as a treatment for deep dermal burns because it has the effectiveness of epithelial formation in deep dermal burns. Further research needs to be done on the higher degree of burns as well as research on the side effects that may be caused during honey administration. Further studies standardize the composition and effective dose of honey for the treatment of burns so that it is used by the standard treatment standards for burns.